Microbial communities of the Lemon Creek Glacier show subtle structural variation yet stable phylogenetic composition over space and time - Sheik, Cody S.; Stevenson, Emily I.; Den Uyl, Paul A.; Arendt, Carli A.; Aciego, Sarah M.; Dick, Gregory J. (Frontiers in Microbiology, 2015)
Glaciers are geologically important yet transient ecosystems that support diverse, biogeochemically significant microbial communities. During the melt season glaciers undergo dramatic physical, geochemical and biological changes that exert great influence on downstream biogeochemical cycles. Thus, we sought to understand the temporal melt-season dynamics of microbial communities and associated geochemistry at the terminus of Lemon Creek Glacier (LCG) in coastal southern Alaska. Due to late season snowfall, sampling of LCG occurred in three interconnected areas: proglacial Lake Thomas, the lower glacial outflow stream and the glacier’s terminus. LCG associated microbial communities were phylogenetically diverse and varied by sampling location. However, Betaproteobacteria, Alphaproteobacteria and Bacteroidetes dominated communities at all sampling locations. Strict anaerobic groups such as methanogens, SR1, and OP11 were also recovered from glacier outflows, indicating anoxic conditions in at least some portions of the LCG subglacial environment. Microbial community structure was significantly correlated with sampling location and sodium concentrations. Microbial communities sampled from terminus outflow waters exhibited day-to-day fluctuation in taxonomy and phylogenetic similarity. However, these communities were not significantly different from randomly constructed communities from all three sites. These results indicate that glacial outflows share a large proportion of phylogenetic overlap with downstream environments and that the observed significant shifts in community structure are driven by changes in relative abundance of different taxa, and not complete restructuring of communities. We conclude that LCG glacial discharge hosts a diverse and relatively stable microbiome that shifts at fine taxonomic scales in response to geochemistry and likely water residence time.